Carbon dioxide utilization via carbonate-promoted C–H carboxylation - Banerjee, Aanindeeta; Dick, Graham R.; Yoshino, Tatsuhiko; Kanan, Matthew W. (Nature (London), 2016)
Molten salts at intermediate temperatures enable efficient carbonate-promoted carboxylation of very weakly acidic C–H bonds, revealing a new way to transform inedible biomass and carbon dioxide into valuable feedstock chemicals. CO 2 as a chemical feedstock The idea that the greenhouse gas carbon dioxide might be used as a source of feedstock chemicals is attractive but usually impractical — although it reacts readily with carbon-centred nucleophiles, generating the nucleophiles requires a high energy input. But now, inspired by the RuBisCO enzyme which catalyses carbon fixation in plants, Aanindeeta Banerjee et al . demonstrate that molten salts containing alkali metals at intermediate temperatures enable efficient carbonate-promoted carboxylation of very weakly acidic C–H bonds. The potential of this chemistry was illustrated by converting 2-furoic acid (readily made from inedible biomass) into the useful bio-based feedstock furan-2,5-dicarboxylic acid. Using carbon dioxide (CO 2 ) as a feedstock for commodity synthesis is an attractive means of reducing greenhouse gas emissions and a possible stepping-stone towards renewable synthetic fuels 1 , 2 . A major impediment to synthesizing compounds from CO 2 is the difficulty of forming carbon–carbon (C–C) bonds efficiently: although CO 2 reacts readily with carbon-centred nucleophiles, generating these intermediates requires high-energy reagents (such as highly reducing metals or strong organic bases), carbon–heteroatom bonds or relatively acidic carbon–hydrogen (C–H) bonds 3 , 4 , 5 . These requirements negate the environmental benefit of using CO 2 as a substrate and limit the chemistry to low-volume targets. Here we show that intermediate-temperature (200 to 350 degrees Celsius) molten salts containing caesium or potassium cations enable carbonate ions (CO 3 2– ) to deprotonate very weakly acidic C–H bonds (p K a > 40), generating carbon-centred nucleophiles that react with CO 2 to form carboxylates. To illustrate a potential application, we use C–H carboxylation followed by protonation to convert 2-furoic acid into furan-2,5-dicarboxylic acid (FDCA)—a highly desirable bio-based feedstock 6 with numerous applications, including the synthesis of polyethylene furandicarboxylate (PEF), which is a potential large-scale substitute for petroleum-derived polyethylene terephthalate (PET) 7 , 8 . Since 2-furoic acid can readily be made from lignocellulose 9 , CO 3 2– -promoted C–H carboxylation thus reveals a way to transform inedible biomass and CO 2 into a valuable feedstock chemical. Our results provide a new strategy for using CO 2 in the synthesis of multi-carbon compounds.